Adherence by orthopaedic surgeons to AHPRA and Australian Orthopaedic Association advertising guidelines. Issue 5 (8th April 2022) - Ryan, Hannah Y; Sun, Geoffrey Y; Monuja, Masiath; Gillespie, Michael; Burns, Alexander; Solomon, Michael; Adie, Sam
Abstract: Objectives: To examine adherence to Australian Health Practitioner Regulation Agency (AHPRA) and Australian Orthopaedic Association (AOA) advertising guidelines by AOA members. Design, setting: Cross‐sectional survey, Australia. Participants: Two samples of AOA member orthopaedic surgeons: 81 randomly selected from a list of AOA members with publicly available contact details (AOA random sample); and a sample obtained by searching with Google for "orthopaedic surgeon" and the name of the major city in each of the eight Australian states and territories in turn; the top eight results for each search were considered for inclusion (AOA Google sample). Main outcome measures: Non‐compliance of advertising material, by surgeon sample, with the AHPRA and AOA guidelines; associations between non‐compliance and sample, state, location (metropolitan, regional), and subspecialty. Results: Of the 81 surgeons in the AOA random sample, 52 (64%) were non‐compliant with at least one aspect of the AHPRA guidelines, and 53 (65%) were non‐compliant with at least one aspect of the AOA guidelines. Of the 59 surgeons in the AOA Google sample, 48 were non‐compliant with the AHPRA guidelines (81%) and 46 with the AOA guidelines (78%). Incidence of non‐compliance with the AHPRA guidelines was influenced by sample source (AOA Google v AOA random: incidence rate ratio [IRR], 1.37; 95% CI, 1.01–1.87), but not non‐compliance with the AOA guidelines (IRR, 1.09; 95% CI, 0.77–1.55). Conclusion: A large proportion of AOA members who advertise online do not comply with AHPRA and AOA advertising guidelines.